AN EVALUATION OF THE ROLE OF INSTRUCTIONAL LEADERSHIP ON THE PERFORMANCE OF SCHOOLS IN ZIMBABWE - SANDADA, Maxwell; MAKAMANI, Mwanyara (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2016)
The purpose of this research was to investigate the extent to which instructional leadership is contributing to the performance of schools in Zimbabwe. The research was prompted by the little body of knowledge about the phenomenon in Zimbabwe. The study adopted a quantitative approach. A self-administered survey was conducted to collect data from three strata; council primary schools, government primary schools and secondary government schools. Data was analysed using descriptive, correlation and regression analyses. The findings of the study revealed that instructional leadership significantly contributes to both dimensions of school performance: teacher and pupil performances. The results provide some invaluable insights on how school leaders can improve the performance of schools through instructional leadership. Given the robust relationship between instructional leadership and school performance, the school heads should consider to use instructional leadership style in order to enhance the performance of their schools. ABSTRAKT. Der Zweck dieser Forschung war es, zu untersuchen, inwieweit die Führungskompetenz der Leitung der Schule in Simbabwe beitragend. Die Forschung erfolgte aufgrund der wenige gemeinsame Erkenntnisse über das Phänomen in Simbabwe. Die Studie hat einen quantitativen Ansatz angenommen. Eine selbstverwaltete Umfrage wurde durchgeführt, um Daten aus drei Schichten zu sammeln; staatliche Grundschule, Regierungsschule und sekundär Regierungsschule. Die Auswertung der Daten erfolgte mit den Deskriptiv-, Korrelations- und Regressionsanalyse. Die Ergebnisse der Studie enthüllt dass, die Fuhrungskompetenz erheblich den beiden Dimensionen von Schulaufführung beiträgt: Lehrer- und Schule- Aufführung. Die Ergebnisse geben unschätzbare Einblicken wie die Schulleiter ihre Aufführung durch die Führungskompetenz verbessern können. Angesichts des robusten Beziehungen zwischen Führungskompetenzen und Schulaufführung, die Schulleiter sollen berücksichtigen, den Führungsskompetenzenstil zu verwenden, zur Verstärkung der Aufführung ihren Schulen. Schlüsselwörter: Führung, Transformationale Führung, Aufführung, Schule